The Functions Of Taboo Words And Their Translation In Subtitling: A Case Study In â€œThe Helpâ€ - Agus Darma Yoga Pratama (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2016)
Translating taboo words in subtitling especially translating them into Indonesian is quite difficult since most of the Indonesian people are not used to utter taboo or offensive words publicly. In addition, watching movie is more of social activity compared to reading and that is why reading taboo expressions while watching might be embarrassing. This is why this study tries to explore the functions of the taboo words found in â€œThe Helpâ€ movie and tries to find out how the translator translate the taboo words into the target language in order to produce the closest functions to the source language without ignoring the technical aspects of subtitling. This study also deals with the strategy used by the translator to translate the taboo words. The main theories proposed herein are from Karamitroglou (1998), Ljung (2011), Toury (1995), and Gottlieb (1992).Â Â Â Â Â Â Â Â Â Â Â There are 69 taboo words found in the raw data and the functions of those taboo words are to express sympathy, surprise, disappointment, disbelief, fear, annoyance, metaphorical interpretation, reaction to mishap, to emphasize the associated item, function as adjectival intensifier, name-calling, anaphoric use of epithet, oath, curse, unfriendly suggestion, and four of the taboo words show non-swearing word or in dysphemism form. The strategies applied are omission (17), transfer (27), and euphemism (25). In terms of the technical aspect in subtitling, all of the subtitles in the target language are presented at the maximum of two lines at once. However, there are three lines of the subtitles which exceed the maximum numbers of characters being proposed.Â Â Â Â Â Â Â Â Â Â Â Since taboo word is not only used to offend someone, it is important for the translator to get the closest equivalence in the target language in order to maintain its function. The translator may choose whether he/she wants to follow the source language norms to produce adequate target text or follow the target language norms in order to produce acceptable target text.Â Keywords: translation strategy, subtitling, taboo word, dysphemism, omission, transfer, euphemism